2020
DOI: 10.1111/1365-2435.13545
|View full text |Cite
|
Sign up to set email alerts
|

What explains vast differences in jumping power within a clade? Diversity, ecology and evolution of anuran jumping power

Abstract: 1. Anuran (frog and toad) jumping power varies greatly across species, yet muscle power does not. Given that the jumping power of some species is up to five times higher than typical muscle power, power amplification by elastic elements is suggested to explain this discrepancy. However, the ecological reasons for this variation in jumping power remain unclear. One hypothesis is that small jumpers are limited by the time available to accelerate their body during take-off, leading to small species needing greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
(112 reference statements)
0
22
0
Order By: Relevance
“…leg muscle mass) and species with more than one individual. Additionally, we did not include Astley's (2016) data on Heterixalus alboguttatus because these values showed unusually low performance for this genus; power values were more than an order of magnitude lower than our (DSM's) unpublished data on two other congeners and are inconsistent with all other published data on arboreal frogs of the same body size (Mendoza et al 2020). Overall, our dataset comprised morphological measures and jumping performance from a total of 256 adult anurans from 51 species, which spanned a wide body-size range and were found in a variety of microhabitats.…”
Section: Data Collectionmentioning
confidence: 74%
See 2 more Smart Citations
“…leg muscle mass) and species with more than one individual. Additionally, we did not include Astley's (2016) data on Heterixalus alboguttatus because these values showed unusually low performance for this genus; power values were more than an order of magnitude lower than our (DSM's) unpublished data on two other congeners and are inconsistent with all other published data on arboreal frogs of the same body size (Mendoza et al 2020). Overall, our dataset comprised morphological measures and jumping performance from a total of 256 adult anurans from 51 species, which spanned a wide body-size range and were found in a variety of microhabitats.…”
Section: Data Collectionmentioning
confidence: 74%
“…However, since back muscles make up <0.5% of body mass (Emerson and DeJongh 1980), their contribution to jumping is small compared to leg muscle mass, which makes up 5-30% of body mass in anurans (Mendoza et al 2020). Furthermore, Clemente and Richards (2013) found that plantaris muscle force scaled with body mass to the 0.94 power in Xenopus laevis, and not 2/3 as predicted above by geometric isometry.…”
Section: Morphological Measures Used In Approximationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, in the fossorial Hemisus (Engelkes et al, 2020) and in the semifossorial Hamptophryne (de Sá & Trueb, 1991) and may provide a strong, fixed arch against which the muscles of the shoulder and arm brace to enable digging. These characteristics are seemingly accompanied by a reduction of the size of phalanges, more developed fringes on the fingers, smaller eyes and an increase in body size, altogether suggesting an overall increase of the fossorial habits of these species (Emerson, 1976;Mendoza et al, 2020;Thomas et al, 2020). In contrast, the differences in the posterior part of the body are subtle among all Synapturanus species.…”
Section: Morphological Evolution and Fossoriality In Synapturanusmentioning
confidence: 96%
“…This fusion may thus confer the Synapturanus of the western clade strong jumping abilities related to their leaf-litter habitat (Fabrezi et al, 2017). Mendoza et al (2020) found that jumping power declines more rapidly with body mass in burrowing species of frogs than non-burrowing species and suggested the existence of a functional trade-off between jumping and burrowing performance. Therefore, the smaller size of these species compared to the ones of the eastern clade also strengthens the idea that they are more epigean.…”
Section: Morphological Evolution and Fossoriality In Synapturanusmentioning
confidence: 99%